From Trepidation to Transformation: Strategies Used by Occupational Therapy Students on Role-Emerging Placements - Clarke, Channine; De-Visser, Richard; Sadlo, Gaynor (International Journal of Practice-based Learning in Health and Social Care, 2019)
To prepare graduates for the diverse practice contexts in which they may work in the future, role-emerging placements are increasingly being used within curricula. Literature highlights the benefits and challenges of such placements but there has been little research to examine how students manage and overcome these challenges. Interpretative phenomenological analysis (IPA) was used to gain a deeper understanding of how five MSc pre-registration occupational therapy students coped with the challenges of undertaking a role-emerging placement. Interviews were carried out and analysed using IPA guidelines. The students utilised personal attributes, reflection, supervision, communities of practice, peer support and experiential learning to help them cope with, and overcome, the placement challenges. This enabled them to take ownership of their own learning and development, leading to positive placement outcomes. We conclude that students need to be encouraged to use and develop a range of strategies to overcome challenges of role-emerging placements. The findings build on existing accounts of students’ experiences of role-emerging placements by providing deeper insights into the strategies they use to help them manage such placements successfully. Recommendations for further research are highlighted. Suggestions for placement preparation to facilitate students’ coping strategies are made.